Pengaruh Organizational Citizenship Behavior terhadap Kinerja Karyawan dengan Power Distance sebagai Moderating pada PT Telkom Medan - vara anggia lintang (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2019)
ABSTRACT The assesment of employee performance in a company is very important. Organizational citizenship behavior (OCB) will encourage employee performance individualy or in gropus. However power distance could strengthened or weakness the relationship between OCB and employee performance The research was conducted at PT Telkom Medan. Data collected through distribution of quesionnaries to 196 respondens with random sampling techniques. This research using validity test, realibility test, the classical asumpastion test, regression test, and MRA (Moderated Regression Anlaysis) to test moderating variabel with SPSS 20.0 The results of this research indicates that organizational citizenship behavior have a positive and significant effect on employee performance. And power distance moderate by strengthening the effect of OCB on employee performance.